Process simulation of cassava cellulosic ethanol production with low to medium-pressure steam heat integration - Chaiyanan Kamsuwan; Sorathan Tanprasert; Prathana Nimmanterdwong; Ratchanon Piemjaiswang; Kanokporn Saencharee; Tanakorn Pumchumpol; Benjapon Chalermsinsuwan (Energy Reports, 2023)
Energy demand tends to increase by 80% in 2050 due to the rapid growth of the global population. However, the energy resources rapidly decrease for responding to the global need. Many previous researchers suggest the ideas for solving this situation and the most interesting solution is the heat integration which intends to produce cost-effective energy with minimal impact on the environment. Energy integration thus should be noticeable for the industry process to minimize the loss along the industrial process. The ethanol production process is interested in this study because it can add value to agricultural products like cassava which is an industrial crop in several countries and produces ethanol products that can decrease the usage of gasoline. Here, the heat integration model was developed for the ethanol production process by using low to medium-pressure steam. For the simulation model, the ethanol production process used the cellulose content as the main inlet component to be easy for applicable corresponding to feed casava cellulosic substances. The process contained three sections including enzymatic hydrolysis, simultaneous saccharification fermentation (SSF), and fractional distillation. The quality and quantity of low to medium-pressure steam were investigated for maintaining the operation of the enzymatic hydrolysis reactor by varying steam pressure between 1–2 atm and steam temperature between 100–105 °C. The results achieved the methodology to find optimum conditions by the ratio between steam flow rate and product quantity. The best case could reduce 6.49% of the excessive usage of low to medium-pressure steam which pointed out the way to use the energy efficiently.